ANALISIS PERTUMBUHAN VEGETATIF JAGUNG UNGU PADA BERBAGAI KONSENTRASI NaCl - Fatkhur Robani; Faturrahman Faturrahman; Rahmi Rahmi (Fakultas Pertanian, Universitas Tadulako, 2022)
The aim of the study was to investigate how salinity stress, specifically the addition of NaCl, affects the growth of purple corn plants. The study was conducted between August and November 2020 at the Seed Science Laboratory and Screen house, Faculty of Agriculture, Tadulako University, Palu, and employed a completely randomized design (CRD) with four treatments. The treatments included a control group with no NaCl added (N1), and three experimental groups with increasing levels of NaCl concentration: 1,500 ppm (N2), 3,500 ppm (N3), and 4,500 ppm (N4). Each treatment was replicated five times, making up a total of 20 experimental units. The results of the study indicated that the addition of NaCl had a significant effect on the total dried weight of the purple corn plants. Salinity stress caused poor growth or inhibition of the vegetative organs of the purple corn plants. The study found that the tolerant limit for purple corn to grow in terms of NaCl concentration was 3,500 ppm. Overall, this study provides insights into how salinity stress, specifically through the addition of NaCl, can impact the growth of purple corn plants. The findings suggest that excessive salinity levels can significantly affect plant growth, and that there is a threshold limit for NaCl concentration beyond which the plants become less tolerant.